First Nationalism Then Identity On Bosnian Muslims and Their Bosniak Identity - Krijestorac, Mirsad (Ethnic Conflict: Studies in Nationality, Race, and Culture, 2022)
First Nationalism Then Identity focuses on the case of Bosnian Muslims, a rare historic instance of a new nation emerging. Although for Bosnian Muslims the process of national emergence and the assertion of a new salient identity have been going on for over two decades, Mirsad Kriještorac is the first to explain the significance of the whole process and how the adoption of their new Bosniak identity occurred. He provides a historical overview of Yugoslav and Bosnian Slavic Muslims' transformation into a full-fledged distinct and independent national group as well as addresses the important question in the field of nationalism studies about the relationship between and workings of nationalism and identity. While this book is noteworthy for ordinary readers interested in the case of Bosnian Muslims, it is an important contribution to the scholarly debate on the role of nationalism in the political life of a group and adds an interdisciplinary perspective to comparative politics scholarship by drawing from anthropology, history, geography, and sociology.